African Continental Free Trade Area: Design of Dispute Settlement Mechanism Should Reflect Preferences and Realities of All Its Member States - United Nations Conference on Trade; Development (United Nations, 2023)
The African Continental Free Trade Area is set to promote structural transformation in States parties, in addition to strengthening sustainable and inclusive socioeconomic development and improving gender equality. However, to achieve the desired outcomes and maximize benefits, it is imperative for implementation to be undertaken carefully, with strong and appropriate institutions underpinning the process. A key aspect of any trade agreement involving different parties is the dispute settlement mechanism, aimed at fostering trust, accountability and the rule of law in operationalizing the agreement. UNCTAD, in this policy brief, analyses the framework of the dispute settlement mechanism under the African Continental Free Trade Area Agreement by comparing it with other dispute settlement mechanisms under regional economic communities and the World Trade Organization, with a focus on challenges. In addition, recommendations are made for enhancing the dispute settlement mechanism, to ensure that it is more accessible and aligned with the preferences of member States of the African Continental Free Trade Area.